Association of Initial Disease-Modifying Therapy With Later Conversion to Secondary Progressive Multiple Sclerosis - Brown, J William L; Coles, Alasdair; Horakova, Dana; Havrdova, Eva; Izquierdo, Guillermo; Prat, Alexandre; Girard, Marc; Duquette, Pierre; Trojano, Maria; Lugaresi, Alessandra; Bergamaschi, Roberto; Grammond, Pierre; et al. (JAMA, 2019)
IMPORTANCE: Within 2 decades of onset, 80% of untreated patients with relapsing-remitting multiple sclerosis (MS) convert to a phase of irreversible disability accrual termed secondary progressive MS. The association between disease-modifying treatments (DMTs), and this conversion has rarely been studied and never using a validated definition. OBJECTIVE: To determine the association between the use, the type of, and the timing of DMTs with the risk of conversion to secondary progressive MS diagnosed with a validated definition. DESIGN, SETTING, AND PARTICIPANTS: Cohort study with prospective data from 68 neurology centers in 21 countries examining patients with relapsing-remitting MS commencing DMTs (or clinical monitoring) between 1988-2012 with minimum 4 years' follow-up. EXPOSURES: The use, type, and timing of the following DMTs: interferon beta, glatiramer acetate, fingolimod, natalizumab, or alemtuzumab. After propensity-score matching, 1555 patients were included (last follow-up, February 14, 2017). MAIN OUTCOME AND MEASURE: Conversion to objectively defined secondary progressive MS. RESULTS: Of the 1555 patients, 1123 were female (mean baseline age, 35 years [SD, 10]). Patients initially treated with glatiramer acetate or interferon beta had a lower hazard of conversion to secondary progressive MS than matched untreated patients (HR, 0.71; 95% CI, 0.61-0.81; P < .001; 5-year absolute risk, 12% [49 of 407] vs 27% [58 of 213]; median follow-up, 7.6 years [IQR, 5.8-9.6]), as did fingolimod (HR, 0.37; 95% CI, 0.22-0.62; P < .001; 5-year absolute risk, 7% [6 of 85] vs 32% [56 of 174]; median follow-up, 4.5 years [IQR, 4.3-5.1]); natalizumab (HR, 0.61; 95% CI, 0.43-0.86; P = .005; 5-year absolute risk, 19% [16 of 82] vs 38% [62 of 164]; median follow-up, 4.9 years [IQR, 4.4-5.8]); and alemtuzumab (HR, 0.52; 95% CI, 0.32-0.85; P = .009; 5-year absolute risk, 10% [4 of 44] vs 25% [23 of 92]; median follow-up, 7.4 years [IQR, 6.0-8.6]). Initial treatment with fingolimod, alemtuzumab, or natalizumab was associated with a lower risk of conversion than initial treatment with glatiramer acetate or interferon beta (HR, 0.66; 95% CI, 0.44-0.99; P = .046); 5-year absolute risk, 7% [16 of 235] vs 12% [46 of 380]; median follow-up, 5.8 years [IQR, 4.7-8.0]). The probability of conversion was lower when glatiramer acetate or interferon beta was started within 5 years of disease onset vs later (HR, 0.77; 95% CI, 0.61-0.98; P = .03; 5-year absolute risk, 3% [4 of 120] vs 6% [2 of 38]; median follow-up, 13.4 years [IQR, 11-18.1]). When glatiramer acetate or interferon beta were escalated to fingolimod, alemtuzumab, or natalizumab within 5 years vs later, the HR was 0.76 (95% CI, 0.66-0.88; P < .001; 5-year absolute risk, 8% [25 of 307] vs 14% [46 of 331], median follow-up, 5.3 years [IQR], 4.6-6.1). CONCLUSIONS AND RELEVANCE: Among patients with relapsing-remitting MS, initial treatment with fingolimod, alemtuzumab, or natalizumab was associated with a lower risk of conversion to secondary progressive MS vs initial treatment with glatiramer acetate or interferon beta. These findings, considered along with these therapies' risks, may help inform decisions about DMT selection.
Keywords: Immunologic Factors; Male; kohortové studie; Immunosuppressive Agents; progrese nemoci; imunosupresiva; Cohort Studies; Interferon-beta; fingolimod hydrochlorid; alemtuzumab; Adult; Glatiramer Acetate; dospělí; relabující-remitující roztroušená skleróza; mužské pohlaví; Disease Progression; Multiple Sclerosis, Relapsing-Remitting; Natalizumab; Fingolimod Hydrochloride; lidé; interferon beta; ženské pohlaví; Humans; natalizumab; glatiramer acetát; čas zasáhnout při rozvinutí nemoci; imunologické faktory; Female; Alemtuzumab; Time-to-Treatment